Alcohol septal ablation vs myectomy for symptomatic hypertrophic obstructive cardiomyopathy: Systematic review and meta‐analysis. Issue 1 (29th November 2018) - Osman, Mohammed; Kheiri, Babikir; Osman, Khansa; Barbarawi, Mahmoud; Alhamoud, Hani; Alqahtani, Fahad; Alkhouli, Mohamad
Abstract : Background: Surgical myectomy (SM) and Alcohol septal ablation (ASA) are effective therapies for patients with hypertrophic cardiomyopathy who remain symptomatic despite medical therapy. A plethora of data has recently emerged on the long‐term outcomes of these procedures. We hence sought to perform an updated meta‐analysis comparing both procedures. Methods: Studies reporting long‐term (>3‐years) outcomes of SM and/or ASA were included. The primary endpoint was all‐cause mortality. Secondary endpoints included cardiovascular mortality, sudden cardiac death (SCD), reintervention, and complications including death, pacemaker implantation, and stroke. Results: Twenty‐two ASA cohorts (n = 4213; follow‐up = 6.6‐years) and 23 SM cohorts (n = 4240; follow‐up = 6.8‐years) were included. Septal myectomy was associated with higher periprocedural mortality and stroke (2% vs 1.2%, P = 0.009 and 1.5% vs 0.8% P = 0.013, respectively), but ASA was associated with more need of pacemaker (10% vs 5%, P < 0.001). During long‐term follow‐up, all‐cause mortality, cardiovascular mortality, and sudden cardiac death rates were 1.5%, 0.4%, and 0.3% per person‐year in the ASA group and 1.1%, 0.5%, and 0.3% per person‐year in the SM group ( P = 0.21, P = 0.53, P = 0.43), respectively. Repeat septal reduction intervention(s) were more common after ASA (11% vs 1.5%, P < 0.001). Conclusion: Compared with SM, ASA is associated with lower periprocedural mortality and stroke but higher rates of pacemaker implantations and reintervention. However, there was no difference between ASA and SM with regards to long‐term all‐cause mortality, cardiovascular mortality, or SCD.